Eurocentrism, Qurʾanic translation and decoloniality - Othman, Ahd (Routledge studies in Arabic translation, 2024)
"Eurocentrism, Qur'anic Translation and Decoloniality contributes to the understanding of Eurocentrism in Translation Studies and engages with the concept through the lens of scholarship on Arabic and Qur'an translation. This book calls for a deeper consideration of Eurocentrism as essential for several debates in the discipline, including its scientific character and future development. It claims that the angle of Arabic and Qur'an translation is a valuable - and nearly unexploited - area where tensions in translation scholarship can play out in revealing ways. The book also draws connections between Eurocentrism, Qur'an translation and decolonial thought in order to highlight 'decoloniality' as a useful framework for imagining a post-Eurocentric discipline. The book will appeal to scholars and postgraduate students and researchers interested in Translation Studies, particularly within the areas of Arabic, Qur'anic, Islamic and religious translation"--